Lactobacillus plantarum KSFY06 on d‐galactose‐induced oxidation and aging in Kunming mice. Issue 1 (5th December 2019) - Li, Fang; Huang, Guangbin; Tan, Fang; Yi, Ruokun; Zhou, Xianrong; Mu, Jianfei; Zhao, Xin
Abstract: Yogurt from Xinjiang, China, is a traditional Chinese fermented food rich in beneficial microorganisms, such as Lactobacillus plantarum KSFY06. In this study, the effect of KSFY06 on oxidative aging was investigated using live animal experiments. Molecular biological methods were used to analyze the serum and tissues of mice with oxidative aging induced by d ‐galactose, which showed that KSFY06 can inhibit the decline of heart, liver, spleen, and kidney caused by aging. The KSFY06 strain increased the activity of superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), catalase (CAT), and glutathione (GSH) in serum and liver of aging mice, while the content of malondialdehyde (MDA) is reduced. Pathological observation showed that KSFY06 alleviated damage to the liver, spleen, and skin of oxidative aging mice. qPCR showed that, at high dose (2 × 10 9 cfu/kg per day), KSFY06 upregulates copper/zinc superoxide dismutase (SOD1), manganese superoxide dismutase (SOD2), endothelial nitric oxide synthase (eNOS), neuronal nitric oxide synthase (nNOS), catalase (CAT) mRNA expression, and its downstream inducible nitric oxide synthase (iNOS) mRNA expression in liver and spleen tissues induced by d ‐gal. To a certain extent, these findings indicate that L. plantarum KSFY06 is able to protect against oxidative stress in the d ‐gal‐induced aging model. In conclusion, L. plantarum KSFY06 may provide a potential research value in the prevention or alleviation of related diseases caused by oxidative stress. Abstract : This study explored the effect of KSFY06 on oxidative aging in vivo. KSFY06 may provide a promising dietary approach for the prevention or alleviation of oxidative stress and age‐related conditions.